2010
DOI: 10.1016/j.bbr.2010.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eszopiclone and zolpidem on sleep–wake behavior, anxiety-like behavior and contextual memory in rats

Abstract: At present, eszopiclone and zolpidem are the most commonly prescribed drugs for treating insomnia. Despite the established relationship between sleep disturbance and anxiety, it remains unknown whether targeted treatment for insomnia may affect acute anxiety. Therefore, the objective of this study was to examine the effects of three different doses (1, 3, and 10 mg/kg) of eszopiclone and zolpidem on the states of sleep and wakefulness, levels of anxiety-like behavior, and long-term contextual memory in footsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 102 publications
2
27
0
Order By: Relevance
“…38-41 In addition, intraperitoneal administration of eszopiclone causes anxiolysis. 42 These findings fit with the concept that BZ site agonists produce their desired clinical actions by enhancing GABAergic inhibition, resulting in diminished neuronal excitability within the amygdala. This interpretative view of a mechanism of action of BZ site agonists also is consistent with the present finding that systemically administering midazolam and eszopiclone caused a significant decrease in ACh release in the amygdala of unanesthetized (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…38-41 In addition, intraperitoneal administration of eszopiclone causes anxiolysis. 42 These findings fit with the concept that BZ site agonists produce their desired clinical actions by enhancing GABAergic inhibition, resulting in diminished neuronal excitability within the amygdala. This interpretative view of a mechanism of action of BZ site agonists also is consistent with the present finding that systemically administering midazolam and eszopiclone caused a significant decrease in ACh release in the amygdala of unanesthetized (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Administration of the GABA B agonists sodium oxybate or baclofen before a nap increased SWS, without affecting sleep-dependent declarative memory consolidation of word pairs and face-location associations (1255). In rats, administration of the GABA A agonists eszopiclone and zolipem after learning before sleep impaired contextual memory tested 24 h later (577). Two more recent studies in humans showed similarly impairing effects of triazolam and zolpidem on sleep-dependent consolidation of finger sequence tapping skills (835,836).…”
Section: Gabamentioning
confidence: 95%
“…For power spectral analysis, cortical EEG signals were amplified and bandpass filtered (0.5 – 40 Hz) with a polygraph and Gamma software, as described previously [29, 30]. The amplified and filtered data was digitized at a sampling frequency of 256 Hz and subjected to a Fast Fourier transformation (0.5 – 40 Hz with an interval of 0.2 Hz; using SleepSign software) to calculate the cortical EEG power during the 6-h recording session (bin width of 5 second).…”
Section: Methodsmentioning
confidence: 99%